CARBONATE SYSTEMS ALONG NUTRIENT AND TEMPERATURE GRADIENTS: SOME SEDIMENTOLOGICAL AND GEOCHEMICAL CONSTRAINTS - Mutti M.; Hallock P. (My University, 2003)
Research over the past several decades has clearly demonstrated that changes in the ocean environment have had major impacts on carbonate systems. Changes in climate, ocean circulation and seafloor spreading rates have influenced temperature and seawater chemistry, including carbonate saturation state and nutrient availability, and thereby have determined boundary conditions for the biota that form carbonate platforms. In turn, the biota determine accumulation rates and facies zonations, thus controlling platform geometry and facies dynamics. In the first section of this paper, we examine how nutrient availability influences carbonate facies associations. We first discuss the role of temperature and nutrient gradients in the modern ocean and their influence on biotic associations. Then we discuss how carbonate sedimentation can be characterized along nutrient gradients. In the second section, we review proxies currently used to reconstruct paleoproductivity in open ocean environments and discuss their applicability to neritic carbonate systems. We highlight the variety of existing proxies and their limitations, and suggest that multiple lines of evidence are needed for valid interpretations. Our short review discusses sedimentological, biogenic, and geochemical proxies that can be used to reconstruct past nutrient fluxes and to constrain paleoceanographic controls over the distribution of carbonate associations. However, it also reveals that more data and case studies are needed that integrate shallow and deep water carbonate sequences and elucidate the links between temperature vs. nutrient supplies changes and facies in ancient carbonate sequences.